ePoster: Managing industrial attachment records student' perceptions in optimising Online Repository Automated System / Syarin Sulaiman, Dr. Azlina Bujang, Aiza Johari, Zainon Haji Bibi and Mohd Syazwan Mohd Aris - Sulaiman, Syarin; Bujang, Azlina; Bibi, Zainon; Mohd Aris, Mohd Syazwan (2022)
The study aims to discuss the students' perceptions towards the implementation of automated system in helping the organization to manage records and documents, in which relate to practical or industrial training. Students who are registering for practical/industrial training have increased every semester, therefore the amount of data to be recorded has also increased. In the search of systematic and cost-effective ways of managing the information, there is a need to overcome the problem of keying data into the system and managing the filing manually. In consequence, this study would examine whether the development of automation system has significantly made the data management more efficient and effective (data collection, data storage and data retrieval). From the evaluation, 200 students' perceptions from the implementation were analyzed where the surveys were distributed to the students of random programmes in Universiti Teknologi MARA Sarawak. The findings indicated that the implementation of such application could contribute to the improvement of the information resources of the practical/industrial attachment students. This further ensures that the connection between the faculty and the students is uninterrupted. Apart from that, a good industrial relationship between the management and organization can also be established.The study's outcome indicates positive perceptions and responses from the student users which could impact the development of the application.Thus, the implementation of the proposed system should be used continuously as an automated information delivery tool.